2008
DOI: 10.1128/jvi.02651-07
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Dysfunction in Lyssavirus-Induced Apoptosis

Abstract: Lyssaviruses are highly neurotropic viruses associated with neuronal apoptosis. Previous observations have indicated that the matrix proteins (M) of some lyssaviruses induce strong neuronal apoptosis. However, the molecular mechanism(s) involved in this phenomenon is still unknown. We show that for Mokola virus (MOK), a lyssavirus of low pathogenicity, the M (M-MOK) targets mitochondria, disrupts the mitochondrial morphology, and induces apoptosis. Our analysis of truncated M-MOK mutants suggests that the info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
54
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 59 publications
3
54
0
Order By: Relevance
“…In both cases, we found a highly significant rise in caspase-3 activity at 12 hpi (P Ͻ 0.01). In order to prove that caspase-3 plays a pivotal role in CHPV-mediated neurodegeneration, it was knocked down using esiCaspase-3 (endoribonuclease-prepared siRNA) in Neuro2A cells (34). It was observed that there is a significant downregulation in cleaved caspase-3 and its downstream molecule cleaved PARP in immunoblot analysis at 12 hpi (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In both cases, we found a highly significant rise in caspase-3 activity at 12 hpi (P Ͻ 0.01). In order to prove that caspase-3 plays a pivotal role in CHPV-mediated neurodegeneration, it was knocked down using esiCaspase-3 (endoribonuclease-prepared siRNA) in Neuro2A cells (34). It was observed that there is a significant downregulation in cleaved caspase-3 and its downstream molecule cleaved PARP in immunoblot analysis at 12 hpi (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Viruses are obligatory intracellular parasites, and they modulate the host's intracellular machinery in their favor to prolong their survival (34)(35)(36). An important armory in their arsenal is modu- lation of apoptosis in order to complete their replicative cycle and kill the host when it requires releasing its matured replicates for further invasion (37)(38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…M is essential for virus assembly and release (32) and is able to support virus budding even in the absence of G (31). In addition, RABV M regulates viral RNA synthesis (14,17) and has been described to contribute to TRAIL-dependent induction of apoptosis (25) and to mitochondrial dysfunction (18). Recently, the X-ray crystal structure analysis of M of genotype 2 Lagos bat lyssavirus demonstrated a high conservation of M structures within the rhabdovirus family, despite the lack of sequence conservation between the lyssavirus and vesiculovirus genera (19).…”
mentioning
confidence: 99%
“…The nonstructural protein 3A of hepatitis C virus accumulates on mitochondria, rendering the cells sensitive to apoptosis (35). The matrix protein of Mokola virus, a low-pathogenicity lyssavirus, promotes apoptosis by targeting subunit 1 of the cytochrome c oxidase of the mitochondrial respiratory chain (14). The small PB1-F2 protein of influenza A virus and the viral protein R (Vpr) of human immunodeficiency virus type 1 promote apoptosis by interaction with the adenine nucleotide translocator and the voltage-dependent anion channel 1 components of the permeability transition pore (PTP) complex and significantly contribute to the pathogenic potential of these viruses (6,25,54).…”
mentioning
confidence: 99%